2019
DOI: 10.1002/art.40935
|View full text |Cite
|
Sign up to set email alerts
|

A Link Between Plasma Microbial Translocation, Microbiome, and Autoantibody Development in First‐Degree Relatives of Systemic Lupus Erythematosus Patients

Abstract: Objective Systemic lupus erythematosus (SLE) is characterized by the production of antibodies against self antigens. However, the events underlying autoantibody formation in SLE remain unclear. This study was undertaken to investigate the role of plasma autoantibody levels, microbial translocation, and the microbiome in SLE. Methods Plasma samples from 2 cohorts, one with 18 unrelated healthy controls and 18 first‐degree relatives and the other with 19 healthy controls and 21 SLE patients, were assessed for au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(56 citation statements)
references
References 50 publications
6
46
0
Order By: Relevance
“…To account for all of these findings, we envision that, in susceptible humans and mice, a genetic predisposition for immune dysfunction may increase the host exposure to nucleic acid material during infections and trigger a lymphocyte repertoire already prone to autoreactivity in the presence of specific HLA haplotypes, while in non-autoimmune-prone humans and mice, infections normally result in less prolonged exposure of a repertoire more self-tolerant to nucleic acid material. This is supported by reports of high levels of circulating endotoxin and more frequent bacteremia in SLE patients (68, 69, 89, 104).…”
Section: Infections As Environmental Pathogenic Factorsupporting
confidence: 73%
See 1 more Smart Citation
“…To account for all of these findings, we envision that, in susceptible humans and mice, a genetic predisposition for immune dysfunction may increase the host exposure to nucleic acid material during infections and trigger a lymphocyte repertoire already prone to autoreactivity in the presence of specific HLA haplotypes, while in non-autoimmune-prone humans and mice, infections normally result in less prolonged exposure of a repertoire more self-tolerant to nucleic acid material. This is supported by reports of high levels of circulating endotoxin and more frequent bacteremia in SLE patients (68, 69, 89, 104).…”
Section: Infections As Environmental Pathogenic Factorsupporting
confidence: 73%
“…The gut microbiota have been subject of intense investigation because of the intriguing findings that gut dysbiosis has local and systemic effects on the immune system (8184), but microbiota also reside beyond the gut, colonizing mucosal tissues and specific niches, from the skin to oral cavity, vagina, or the bladder, where they are expected to exercise major effects as well (85). Studies focused on lupus specifically found a reduction in species diversity in the gut microbiota that is associated with specific enteric bacteria in SLE patients (8688) or their first-degree relatives (89) and was present in cohorts from different continents with different ethnicities (90). DNA from Enterococcus gallinarum was found in the liver of SLE patients, and colonization of autoimmune-prone mice with these bacteria induced autoantibodies and decreased survival (91).…”
Section: Microbiome and Lupusmentioning
confidence: 99%
“…Many studies have showed that race/ethnicity has significant effects not only on manifestations, complications, and prognosis of SLE (5-7), but also on microbiota in various populations (8). Moreover, in this study, plasma LPS levels appeared to be lower (as seen in Figures 2A and B) and microbiota diversity appeared higher (as seen in Figures 5A and B) in unrelated healthy controls of the first cohort than in those of the second cohort (4). As a result, it is very possible that the difference in genetic background leads to the divergence in the results between first-degree relatives and SLE patients.…”
Section: To the Editorsupporting
confidence: 51%
“…E coli and S typhimurium –representing 2 members of the Enterobacteriaceae family–are characterized by the production of curli/eDNA complexes and form biofilms that are associated with bacteremia in SLE (33). Interestingly, activation of the innate immune system by bacteremia is supported by studies showing that lupus patients have increased plasma levels of lipopolysaccharide and that the peripheral blood mononuclear cells of lupus patients exhibit a transcriptome suggestive of chronic exposure to bacterial products (34,35). We have previously demonstrated that systemic injection of curli/eDNA complexes accelerated the pathologic development of lupus in lupus‐prone mice, as did systemic infections with E coli or S typhimurium , in a curli‐dependent manner (12).…”
Section: Discussionmentioning
confidence: 99%